PENGATURAN RUANG KELAS MENURUT CONNY SEMIAWAN DKK - Dwi, Alfani; Rizkyta Siregar, Nova Dwi; Tanjung, Rida Salmiah; Rizkyta Siregar, Sintya (PROGRAM STUDI MANAJEMEN PENDIDIKAN ISLAM, 2023)
At this time, teachers must be good at arranging classrooms so that their students can feel comfort and peace, so that the classes that are neatly arranged will have an impact on the ease of students in receiving learning or imitating the material that has been delivered by the teacher. The method that the author uses is a literacy study approach method which takes from reference materials for journal books and others. The definition of Classroom Arrangement in Classroom Management is to create an exciting learning atmosphere and allow children to sit in groups, making it easier for teachers to move powerfully to help students in learning. Who pays attention to the following: The size and shape of the class, the shape and size of the student's bench and desk, the number of students in the class, the number of students in each group, the number of groups in the class, the composition of the students in the group. The arrangement of the physical environment of the classroom is related to the creation of a good environment by designing student seats to create a classroom atmosphere that can encourage students to learn well.